Adopting an ethical approach to migration health policy, practice and research - Onarheim, Kristine Husøy (BMJ Glob Health, 2021)
Migration health is affected by decision making at levels ranging from global to local, both within and beyond the health sector. These decisions impact seeking, entitlements, service delivery, policy making and knowledge production on migration health. It is key that ethical challenges faced by decision makers are recognised and addressed in research and data, clinical practice and policy making on migration health. An ethical approach can provide methods to identify ethical issues, frameworks for systematising information and suggesting ethically acceptable solutions, and guidance on procedural concerns and legitimate decision making processes. By unpacking dilemmas, conflicts of interests and values at stake, an ethical approach is relevant for all who make decisions about migration health policy and practice. Adopting an ethical approach to migration health benefits governments, organisations, policy makers, health workers, data managers, researchers and migrants themselves. First, it highlights the inherent normative questions and trade-offs at stake in migration health. Second, it assists decision makers in deciding what is the ethically justifiable thing to do through an ‘all things considered’ approach. Third, ethical frameworks and technical guidance set normative and practical standards for decision makers facing ethical questions – from ‘bedside rationing’ to collection of big data or in policy making – that can ensure that migrants’ interests are considered. Fourth, there is a need for greater transparency and accountability in decision making, as well as meaningful participation of migrant groups. An ethical approach connects to public health, economic and human rights arguments and highlights the urgent need to mainstream concerns for migrants in global and national health responses.